호텔 총지배인의 겸손리더십이 구성원의 번영감과 창의적 행동에 미치는 영향 - 이상우(Sang-Woo Lee) (인문사회과학연구, 2022)
· 연구 주제: 겸손리더십, 번영감, 창의적 행동과의 영향관계를 검증하여 호텔의 인적자원관리에 대한 시사점을 제시하였다. · 연구 배경: 호텔을 대상으로 한 겸손리더십 관련 연구가 미미하여 겸손리더십의 결과 변수에 대한 실증분석을 진행하였다. · 선행연구와의 차이점: 호텔을 대상으로 한 겸손리더십 관련 연구를 확장하여 후속 연구에 기여하였다. · 연구방법: 타당성분석, 신뢰성분석, 확인적 요인분석, 상관관계분석, 구조방정식 모형분석을 활용하였다. · 연구결과: 겸손리더십은 번영감과 창의적 행동에 정(+)의 영향을 나타냈고, 번영감도 창의적 행동에 정(+)의 영향을 나타냈다. 이러한 결과를 바탕으로 호텔 경영성과 향상을 위한 시사점을 제시하였다. · 공헌점 및 기대효과: 겸손리더십과 번영감, 창의적 행동에 대한 검증을 통해 구성원의 자존감 및 자기주도적 행동을 향상 시킬 수 있는 대안과 기존 선행연구와의 차별점 및 본 연구의 의의를 강조하여 후속 연구에 대한 필요성을 언급하였다. · Research topics: To investigate the relationship between humility leadership, thriving at work and creative behavior, we present implications for hotel human resource management. · Research background: There are few studies on humility leadership targeting hotels, and the management performance of hotels can be improved by verifying outcome variables related to humility leadership. · Differences from prior research: Since there are few prior studies on humility leadership targeting hotels, it is expected that various studies will be possible through this study. · Research method: Validity analysis, reliability analysis, confirmatory factor analysis, correlation analysis, and structural equation model analysis were used. · Research results: Humility leadership showed a positive(+) effect on a thriving at work and creative behavior and a thriving at work showed a positive(+) effect on creative behavior. · Contribution points and expected effects: By examining the relationship between humility leadership, a thriving at work and creative behavior, the implications for improving hotel management performance were presented through alternatives that could improve members' self-esteem and self-directed behavior. KCI Citation Count: 0